Impact of density loads on performance of duckweed bioreactor: A potential system for synchronized wastewater treatment and energy biomass production. Issue 6 (9th June 2015) - Verma, Rashmi; Suthar, Surindra
Abstract : Duckweed Lemna gibba has been listed as a promising plant for wastewater treatment and energy biomass production. This study aims to study the efficacy of L. gibba based bioreactor in removal of wastewater pollutants loads and energy‐rich biomass harvesting under different plant biomass density loads. A total of four density loads: 20% (T1), 40% (T2), 60% (T3), and 80% (T4) of inoculants biomass were used to construct duckweed reactors and changes in wastewater (WW) and duckweed biomass characteristics (growth rate, biochemical composition etc.) were recorded for 21 days. The nutrient load in WW reduced significantly: NO3−N (83–89%), SO4 2– 30 (85–86%) and total phosphorus (TP) (67–72%) at the end in all experimental set‐ups. The reactor with 20% inoculation density showed the maximum WW nutrient removal. The weed biomass yield showed the direct relationship with inoculation density in all experimental set‐ups. The yield (dry weight basis) of carbohydrate, starch and protein was: 1.39–1.77 g m −2  day −1, 1.10–1.20 g m −2  day −1, and 1.9–2.24 g m −2  day −1, respectively in different set‐ups. The high yield of starch under optimized density load suggests the utility of harvested biomass for bioethanol production. Results thus, suggested that inoculation density directly plays an important role in performance of duckweed reactors in terms of WW treatment and energy biomass synthesis. © 2015 American Institute of Chemical Engineers Environ Prog, 34: 1596–1604, 2015